Quantifying the effects of higher world oil prices on recource allocation and living standards in an energy poor open economy - David P. Vincent (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
The OPEC Cartel's spectacular success in raising real world oil prices over the past decade has brought about substantial net resource transfers from energy poor to energy rich countries within the world economy. In accomodating these resource transfers both energy exporting and importing economies have been confronted with adjustment pressures. Of course the intensity and nature of these adjustment pressures has differed substantially between countries according to amongst other things a country's resource endowment, its net trade position with respect to oil and other energy based products and the degree of openness of its economy to world trade. Our concern in this paper is with quantifying the short and medium term adjustment pressures imposed on the South Korean economy assuming continued increases in real world oil prices. The results are derived from a multisectoral general equilibrium model. A feature of the model is its design flexibility and simple solution algorithm. We exploit this in the present study by comparing results for a range of experiments to accommodate differing assumptions about the Korean macroeconomic environment, labour market behaviour and Korean export demand. While the numerical results refer specifically to Korea, it is to be hoped that by rationalising them in terms of the underlying structural features inherent in the Korean economy the paper provides some guidance on the sorts of adjustment pressures likely to confront energy poor open economies assuming a continued movement in the world terms of trade towards oil.
Keywords: 330